Zusammenarbeit in St. Gallen: Christoph Schappeler und Joachim von Watt (Vadian) über das Gebet - Stettler, Bernhard (Zwingliana, 2016)
Christoph Schappeler had written a tract on prayer to return it “to the old and proper track” according to the intentions of the Reformers; Joachim von Watt (Vadian) copied this tract and revised it thoroughly. Schappeler’s original is no longer extant; the manuscript with the number 53 of the Vadian collection in the canton library of St Gallen is written in its entirety in the hand of Vadian. The non-theologian Vadian, who had already commented multiple times previously on religious topics, thus engaged with a topic of ecclesiastical practice – from prayer and the veneration of the saints, via the singing during worship to the prayer at places of pilgrimage. During his revision, Vadian visibly makes the text his own and introduces his own, Reformed concerns. Schappeler had directed his tract at the “readers in Germany”; Vadian may have addressed “the reader” repeatedly, but a publication of the tract after his revision was no longer conceivable.